2017
DOI: 10.1080/09638199.2017.1386230
|View full text |Cite
|
Sign up to set email alerts
|

Domestic institutions and export performance: Evidence for Cambodia

Abstract: The paper analyzes the relevance of domestic institutions for export performance of Cambodia. Regulatory quality, control of corruption, rule of law, government effectiveness and political stability are introduced in an augmented gravity model with a panel data set over 1996-2015. The research is the first application to Cambodia, until 2015 a least developed country which is generally believed to have poorly developed institutions. Due to high multicollinearity among the variables, the institutional variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 45 publications
1
12
0
1
Order By: Relevance
“…The model has been widely applied in the estimations and projections of aggregate trade. Several authors, for instances, Nanovsky (2019), Zhou et al (2019), Li, Sun and Long (2019), Shahriar, Qian and Kea (2019), Soeng and Cuyvers (2018), Narayan and Nguyen (2016), Atif et al (2017), Filippini and Molini (2003), Poncet (2006), Batra (2006); Zhou et al (2019); Mitra et al (2018), Gashi et al (2016); Hasiner and Yu (2018) and Ghazalian (2019) applied the model in their empirical works of international trade. The literature is, however, scant in the analysis of the Chinese OFDI along the BRI through an application of the gravity model.…”
Section: Methodsmentioning
confidence: 99%
“…The model has been widely applied in the estimations and projections of aggregate trade. Several authors, for instances, Nanovsky (2019), Zhou et al (2019), Li, Sun and Long (2019), Shahriar, Qian and Kea (2019), Soeng and Cuyvers (2018), Narayan and Nguyen (2016), Atif et al (2017), Filippini and Molini (2003), Poncet (2006), Batra (2006); Zhou et al (2019); Mitra et al (2018), Gashi et al (2016); Hasiner and Yu (2018) and Ghazalian (2019) applied the model in their empirical works of international trade. The literature is, however, scant in the analysis of the Chinese OFDI along the BRI through an application of the gravity model.…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding, the gravity model has a good ability to explain the determinants of international trade, and this model is also flexible enough to adjust to the characteristics of variables and data. Several independent variables in the research model of Soeng and Cuyvers (2018) and Trung et al (2018) were selected to be used in the present study, based on two main considerations: (a) adjusting to the research objectives and (b) its relevance to the Indonesian context as a number of studies examining Indonesia's export performance have found that internal conditions are one of the main constraining factors for Indonesian exports. For instance, those two studies did not include the tariff variable in their research.…”
Section: Methodology and Data Analysismentioning
confidence: 99%
“…The WGI measure institutional governance using 6 dimensions, namely, Voice and Accountability, Political Stability and Absence of Violence / Terrorism, Government Effectiveness, Regulatory Quality, Rule of Law, and Control of Corruption. Studies using these data include Babecká Kucharčuková et al (2012); Gani and Prasad (2006); Iwanow and Kirkpatrick (2007); Méon and Sekkat (2008); and Soeng and Cuyvers (2018). Empirical studies utilising these data are among the most widely used, although with different variations in the use of the index between studies where some use only a few indexes.…”
Section: Graph 2 Six Dimensions Of Institutions Quality In Indonesia Source: Worldwide Governance Indicatorsmentioning
confidence: 99%
“…Fakher (2014), kurumlar ve uluslararası ticaret arasındaki ilişkiyle ilgili yapılan ampirik analizlerin genel geçer bir sonuç üretmediğini, kimi çalışmalarda uluslararası ticaret ile kurumlar arasında pozitif, kimi çalışmalarda negatif, bazılarında ise anlamsız sonuçlar elde edildiğini vurgulamaktadır. Uluslararası ticaret ve kurumlar arasındaki ilişkiyi inceleyen başlıca çalışmalar, Soenga and Cuyvers (2018), Me´On and Sekkat (2008), Zarzoso and Ramos (2018), Krasniqi and Desai (2017), Faruq (2011), Fakher (2014…”
Section: Literatür Taramasıunclassified